TAMING THE TECHNICAL GENIE - Stanley, Sahayaraj (Asian Horizons, 2016)
Technology rules the world today. While praising the usefulness of technology, the world is at times blind to see the dangers and responsibility that come bundled with this technological gift. Excessive use of technology triggers ethical questions. The sacredness of the human person is threatened. Playing God or replacing God with the Golden Calf seems to be the favourite sport today. The role, the reach and benefit of technology to the poor and vulnerable needs to be discussed and debated. Technology is a genie. Are we masters or slaves — that is the question.